(untitled) (Global Journal of Human-Social Science, 2012)
The paper examined the pre-disposing factors to HIV AIDS vulnerability in the fisheries sector of Kainji Lake Basin Thirty fishing communities were selected for data collection through the use of questionnaires Data were analysed using descriptive statistics correlation and factor analysis The findings revealed level of western education among the respondents is very low The correlation analysis for respondents socio-economic characteristics and HIV AID vulnerability revealed that only the respondents education variable impacted significantly on the level estimated number as well as the HIV AIDS cases reported For the socio - cultural factors contributing to HIV AIDS vulnerability family planning is believed to offend their gods Principal component analysis revealed that risky occupation multiple sexual partners women don t have control believed that family planning is offend the gods forced sex talking to children and engaging in sex before marriage are the principal respondents drive factors that makes fisherfolks vulnerable to HIV AIDS The study made recommendations to addressing HIV AIDS in the area